2021
DOI: 10.1089/whr.2021.0023
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities in Authorship of Invited Manuscripts During the COVID-19 Pandemic

Abstract: Introduction: Women have historically been under-represented in medical literature, particularly prominent in authorship of invited commentaries. With the instantaneous change in work environment forcing Americans to adapt to working at home, many theorize that women will be more adversely affected due to traditional concepts of women being more responsible for the home in addition to work responsibilities. Objective: Understand how women contributed to coronavirus dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…However, these studies either included a broad range of article types such as news and opinions as well as research publications, and/or selected data only on the early months of the pandemic in 2020, or were focused on an individual journal, medical specialty, or geographic region. 8 10 11 12 13 14 15 16 17 18 A more recent large study of first authorship attainment, in PubMed indexed life sciences articles with the term “covid” in the title and/or abstract published up to January 2021, found an overall gender gap in the early periods of the pandemic (1 February to 31 May 2020), but with a trend backwards to expected values over time in various medical disciplines. 14 Two further studies showed no gender disparities in publications in the early months of the pandemic, but these were undertaken only in American journals or in a single specialty, medical imaging.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these studies either included a broad range of article types such as news and opinions as well as research publications, and/or selected data only on the early months of the pandemic in 2020, or were focused on an individual journal, medical specialty, or geographic region. 8 10 11 12 13 14 15 16 17 18 A more recent large study of first authorship attainment, in PubMed indexed life sciences articles with the term “covid” in the title and/or abstract published up to January 2021, found an overall gender gap in the early periods of the pandemic (1 February to 31 May 2020), but with a trend backwards to expected values over time in various medical disciplines. 14 Two further studies showed no gender disparities in publications in the early months of the pandemic, but these were undertaken only in American journals or in a single specialty, medical imaging.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Two further studies showed no gender disparities in publications in the early months of the pandemic, but these were undertaken only in American journals or in a single specialty, medical imaging. 15 19 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Academicians also face many of the challenges for gender equality that impacted those in other professions such as eldercare and childcare. Gender gaps have been shown for academic fields and science [5,13], and COVID-19 has amplified these gender inequalities in academia [14,15] that have been long discussed for decades. Well-known factors for the existing gender inequality are the unequal distribution of care and domestic labor between men and women [16].…”
Section: Introductionmentioning
confidence: 99%